The association of fatty pancreas with subclinical atherosclerosis in nonalcoholic fatty liver disease - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
IntroductionEctopic fat accumulation in many tissues has been shown to be a risk factor for developing cardiovascular disease. No study to date has investigated whether fatty pancreas plays a role in the development of subclinical atherosclerosis. We aimed to assess the relationship between fatty pancreas and subclinical atherosclerosis in patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD) and healthy controls.Patients and methodsOne hundred patients with biopsy-proven NAFLD and 38 healthy controls were included. Transabdominal ultrasonography examination was performed on all the cases with high-resolution ultrasonography (Acuson S3000) using 6mHz convex probes. The measurements of carotid intima-media thickness (CIMT) and carotid-femoral pulse wave velocity (cf-PWV) were performed to investigate the relationship between fatty pancreas and atherosclerosis.ResultsThe rate of newly diagnosed DM and prediabetes in the NAFLD patients was 6 and 21%, respectively. Most of the patients with NAFLD (97%) were found to have an increased echogenicity of the pancreas at ultrasound examination. Grade of fatty pancreas was correlated positively with cf-PWV levels (P<0.05), whereas no correlation was found with CIMT (P>0.05). The presence of fatty pancreas was associated significantly with higher CIMT and cf-PWV levels (P<0.05). The results for cf-PWV and CIMT did not remain significant after adjustment for confounding factors. Although the levels of cf-PWV and CIMT increased with increasing grade of fatty pancreas, there was no significant association.ConclusionWe have shown for the first time that fatty pancreas is a contributing factor for the development of atherosclerosis in patients with NAFLD. This study also confirms the strong association between NAFLD and fatty pancreas.
Keywords: arterial stiffness; atherosclerosis; fatty pancreas; BETA-CELL FUNCTION; INSULIN-RESISTANCE; VASCULAR DAMAGE; GLUCOSE; PROGRESSION; POPULATION; MECHANISMS; PLASMA; MODEL